Some Illusions Are More Inconsistent Than Others. (July 2019) - Smeets, Jeroen B. J.; Brenner, Eli
Illusions are characterized by inconsistencies. For instance, in the motion aftereffect, we see motion without an equivalent change in position. We used a simple pencil-and-paper experiment to determine whether illusions that influence an object's apparent size give rise to equivalent changes in apparent positions along the object's outline. We found different results for two equally strong size illusions. The Ebbinghaus illusion affected perceived positions in a way that was consistent with its influence on perceived size, but a modified diagonal illusion did not affect perceived positions. This difference between the illusions might explain why there are so many conflicting reports about the effects of size illusions on the maximum grip aperture during reach-to-grasp movements.